The Effect Of Transformational Leadership On Employee Performance In Sharia Management Review - Ulin, Tuti Tria (Journal of Business Management, 2024)
This research was conducted to find out how behaviours influence outcomes. Idealisation, inspirational influence are components of transformational leadership. Individual motivation, intellectual stimulation, and partial (dimensional) or equal (general) judgement according to the perceived rating scale Islamic Viewpoint. Differential Development Business and competitive environments are influenced by technology. Quantitative-descriptive methodology was used in this investigation. The research was conducted using a survey approach, which involved selecting a sample of the population and using a questionnaire. Sample assessments, interviews, documentation, and participants' perceptions of Islamic management skills based on Islamic principles were all included in the instrument. Islamic values also include the importance of task completion and management ability.